Protection Measures for Shield Tunneling Closely Under-passing Operating Metro Tunnels in Water-rich Soft Soil Area - MA Xifeng; JIN Hua; ZHOU You; CHEN Shaobo; WANG Yu; WU Yaojie (Chengshi guidao jiaotong yanjiu)
［Objective］ In water-rich soft soil areas, it is difficult to control the deformation of the existing operating metro tunnel structure caused by the construction of the shield tunneling closely under-passing. Therefore, it is necessary to conduct research on corresponding protection measures. ［Method］ Based on a project of Nanjing Metro Line 5 shield tunneling closely under-passing the existing section of Nanjing Metro Line 1, the MIDAS/GTS NX finite element software is used to simulate the construction of the shield tunneling. Then, active protection measures for the existing tunnel and control measures for the shield tunneling of the newly-built tunnel are put forward. The vertical displacement and horizontal convergence of the existing tunnel during the shield under-passing are monitored with construction monitoring methods. ［Result & Conclusion］ The specific construction protection measures are as follows. Before the construction of shield tunneling under-passing, the affected sections of the existing tunnel are reinforced with measures such as micro-disturbance grouting, permanent circumferential supports, and longitudinal tension strips to effectively reduce the tunnel deformation and make it conform to the deformation control standards. During the construction, the earth pressure and the amount of excavated soil are adjusted in real time based on the settlement amount of the existing tunnel, and methods are adopted including synchronous grouting and the distribution of grouting amounts in the upper and lower holes to further control the tunnel deformation. After the completion of construction, against the post-construction settlement problem of the stratum, sufficient grouting material and equipment for reinforcing grouting are prepared inside the tunnel section where the shield tunneling underpasses, and subsequent grouting reinforcement is carried out according to the monitored settlement. The above measures can effectively reduce the impact of the shield tunneling under-passing construction on the existing tunnel.